Hopping mad! - Catchpool, Michael; Roberts, David (Tiger Little press Great britain, 2020)
"Hopping Mad!" is a fun and energetic children's book that introduces young readers to the world of rabbits. This book follows a mischievous rabbit who loves to hop and play. Through its bright illustrations and playful rhymes, this book encourages children to move and have fun.